Исследование гидродинамических характеристик конструкционных капиллярных структур в тепловых трубах - Шевель, Евгений Викторович; Батуркин, Владимир Михайлович (Eastern-European Journal of Enterprise Technologies, 2009)
The results of experimental research of pressure losses at the heat-carrier flow in constructional capillary structures of heat pipes are presented. The obtained data are compared with the results of flow simulation by means of one-, two- and three-dimensional models. The influence of interaction of counter-current flows of liquid and vapor in heat pipe is considered as well.